Targeting SARS‐CoV‐2 viral proteases as a therapeutic strategy to treat COVID‐19. Issue 5 (9th February 2021) - Anirudhan, Varada; Lee, Hyun; Cheng, Han; Cooper, Laura; Rong, Lijun
Abstract: The 21st century has witnessed three outbreaks of coronavirus (CoVs) infections caused by severe acute respiratory syndrome (SARS)‐CoV, Middle East respiratory syndrome (MERS)‐CoV, and SARS‐CoV‐2. Coronavirus disease 2019 (COVID‐19), caused by SARS‐CoV‐2, spreads rapidly and since the discovery of the first COVID‐19 infection in December 2019, has caused 1.2 million deaths worldwide and 226, 777 deaths in the United States alone. The high amino acid similarity between SARS‐CoV and SARS‐CoV‐2 viral proteins supports testing therapeutic molecules that were designed to treat SARS infections during the 2003 epidemic. In this review, we provide information on possible COVID‐19 treatment strategies that act via inhibition of the two essential proteins of the virus, 3C‐like protease (3CL pro ) or papain‐like protease (PL pro ). Highlights: This highlights the importance of 3CL pro and PL pro as theraputic targets for drug design and development of SARS‐CoV‐2 inhibitors to prevent COVID‐19.